2011
DOI: 10.1111/j.1365-2966.2011.18876.x
|View full text |Cite
|
Sign up to set email alerts
|

Directed follow-up strategy of low-cadence photometric surveys in search of transiting exoplanets - I. Bayesian approach for adaptive scheduling

Abstract: We propose a novel approach to utilize low‐cadence photometric surveys for exoplanetary transit search. Even if transits are undetectable in the survey data base alone, it can still be useful for finding preferred times for directed follow‐up observations that will maximize the chances to detect transits. We demonstrate this approach through a few simulated cases. These simulations are based on the Hipparcos Epoch Photometry data base and on the transiting planets whose transits were already detected there. In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…They can maximize the probability of detecting actual transit events by selecting follow-up times optimized to their current data and iteratively revise predictions as data accumulates. A Bayesian approach to such a strategy is described in Dzigan & Zucker (2011). In Fig.…”
Section: Detected Periodmentioning
confidence: 99%
“…They can maximize the probability of detecting actual transit events by selecting follow-up times optimized to their current data and iteratively revise predictions as data accumulates. A Bayesian approach to such a strategy is described in Dzigan & Zucker (2011). In Fig.…”
Section: Detected Periodmentioning
confidence: 99%
“…This model involves five parameters: the period -P , phase -Tc, and width of the transit -w, and the flux levels in-transit and ex-transit. The MCMC procedure we chose to use was the Metropolis-Hastings (MH) algorithm (Dzigan & Zucker 2011).…”
Section: Directed Follow-upmentioning
confidence: 99%
“…Due to Gaia's low cadence, and relatively small number of observations per star, in most realistic cases we expect to obtain posterior distributions that will exhibit several possible periods (Dzigan & Zucker 2011). This will result in the other two more probable scenarios:…”
Section: Dfu For Gaiamentioning
confidence: 99%
See 1 more Smart Citation
“…Within Gaia, Tingley (2011) and Dzigan & Zucker (2011) are preparing two different methods to detect such planetary signals. Dzigan & Zucker, using a Bayesian approach, showed that "5 points in a transit deeper than 0.002" means an almost certain detection.…”
Section: Exoplanetsmentioning
confidence: 99%